"redolent of the soil": New Zealand Interior and Landscape Architecture of the 1890s - McCarthy, Christine (Architectural History Aotearoa, 2023)
The 1890s was a period when Pākehā began to strongly identify with New Zealand. There were several reasons for this. By the 1890s a majority of Pākehā had been born in New Zealand, the first generation of Pākehā settlers was passing, the Māori population had dropped, in 1891, to 44,177, and there was a perception by many Pākehā that Māori were a dying race. It was thus considered by many Pākehā that Māori "no longer posed the same threat" as they did during the civil wars, reframing Māori "as a brave and noble race." Smith also writes that "elevating Māori to honorary whites was a further way to render Pākehā superior to white Australians, as well as affirming the long-held belief in a hierarchy of races in which Māori were superior to Aboriginal Australians.